2014
DOI: 10.1186/1750-1326-9-42
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of O-GlcNAcase (OGA) prevents cognitive decline and amyloid plaque formation in bigenic tau/APP mutant mice

Abstract: BackgroundAmyloid plaques and neurofibrillary tangles (NFTs) are the defining pathological hallmarks of Alzheimer’s disease (AD). Increasing the quantity of the O-linked N-acetylglucosamine (O-GlcNAc) post-translational modification of nuclear and cytoplasmic proteins slows neurodegeneration and blocks the formation of NFTs in a tauopathy mouse model. It remains unknown, however, if O-GlcNAc can influence the formation of amyloid plaques in the presence of tau pathology.ResultsWe treated double transgenic TAPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(110 citation statements)
references
References 62 publications
3
103
0
Order By: Relevance
“…Accordingly, decreased O-GlcNAc may thus contribute to the propagation of toxic species in the brain and enable the spread of these hallmark pathologies within the AD brain. Nevertheless, regardless of the precise mechanisms that are operative, the consistent lack of apparent toxicity of OGA inhibitors (48,78,86,94,95,100), coupled with the clear protective effects of perturbing O-GlcNAc cycling, suggests that OGA inhibitors are a promising potential disease-modifying monotherapy for AD and other tauopathies. Such compounds may represent an opportunity to positively influence the toxicity associated with both tau and A␤ and accordingly alter the course of both hallmark pathologies of AD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, decreased O-GlcNAc may thus contribute to the propagation of toxic species in the brain and enable the spread of these hallmark pathologies within the AD brain. Nevertheless, regardless of the precise mechanisms that are operative, the consistent lack of apparent toxicity of OGA inhibitors (48,78,86,94,95,100), coupled with the clear protective effects of perturbing O-GlcNAc cycling, suggests that OGA inhibitors are a promising potential disease-modifying monotherapy for AD and other tauopathies. Such compounds may represent an opportunity to positively influence the toxicity associated with both tau and A␤ and accordingly alter the course of both hallmark pathologies of AD.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study using bigenic TAPP mice, which manifest both amyloid and tau pathologies, reported the effects of longterm OGA inhibition using Thiamet-G (95). OGA inhibition blocked cognitive decline in these mice in parallel to decreases in A␤ levels and amyloid plaques in the brain and showed a clear trend toward decreased Sarkosyl-insoluble tau.…”
Section: O-glcnac and A␤ In Admentioning
confidence: 99%
“…Pharmacological elevation of O‐GlcNAc levels in vivo enhances long‐term potentiation (LTP), whereas reduction in O‐GlcNAc levels blocks LTP (Tallent et al ., 2009). While upregulation of O‐GlcNAcylation pharmacologically prevents cognitive decline and memory impairment in AD transgenic mice (Kim et al ., 2013; Yuzwa et al ., 2014). In the present study, we found that PKAc is modified by O‐GlcNAc.…”
Section: Discussionmentioning
confidence: 99%
“…Another strategy uses an orally available small molecule inhibitor of O-GlcNAase (OGA) to increase O-GlcNAcylation in the brain, which has been shown by several groups to protect against tau and Ab toxicity in preclinical AD mouse models [50]. Studies in bigenic MAPT/APP mutant mice showed that inhibition of OGA prevented cognitive decline and amyloid plaque formation [51] and in JNPL3, tauopathy mice acted to block the formation of hyperphosphorylated tau, the development of tau aggregates, and neurodegeneration [52]. Various protective mechanisms are possible; however, it is interesting to note that O-GlcNAcylation of tau was recently shown to attenuate tau aggregation in vitro [53].…”
Section: Therapeuticsmentioning
confidence: 99%